Employability of academically and vocationally qualified employees - theoretical reflections and empirical evidence from the commerce sector in Germany - Annen, Silvia [Verfasser]; Tiemann, Michael [Verfasser] (My University, 2017)
"Currently there is a debate on the labor market usability of vocational versus academic qualifications in Germany due to changes in the education system. There was a reform of academic qualifications with the introduction of bachelor programs which are ranked on the same level of the German Qualification Framework as vocational further training programs. There are also rising shares of people with a general degree allowing them to attend university and thus it is expected that the shares of graduates from bachelor programs will rise as well. This will possibly lead to competitions on the labor market with persons holding vocational further training certificates. Earlier studies pointed out there might also be a complementarity between the two kinds of educational programs. This paper reports first results from a research multi-method and multi-perspective project aimed at answering the question whether there is complementarity or competition. We contribute to existing literature by analyzing individual educational decisions and career paths. By matching achieved and required qualifications we also consider the quality of employment and labor demand in the sector. We hereby evaluate the usability of qualifications on the labor market." (Authors' abstract, BIBB-Doku)
Keywords: G 1.3.2 Bildungsverhalten und -verläufe; G 1.2.3 Qualifikationsentwicklungen; S 6.4.1 Kaufleute; Bildungsverlauf; Berufsverlauf; Ausbildungsabsolvent; Bachelor; Akademisierung; Arbeitsmarkt; Qualifikationsbedarf; BIBB-/BAuA-Erhebung; Kaufmännischer Beruf